أثر أزمة الديون السيادية على منطقة " اليورو " - الأحمد, محمد; سبور, فراس (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هددت الأزمة اليونانية استقرار منطقة اليورو وطرحت فكرة خروج اليونان من المنطقة الاقتصادية بعدما عصفت أزمة الدين السيادي بالاقتصاد اليوناني في عام 2010، حيث طلبت الحكومة اليونانية من الاتحاد الأوروبي ومن صندوق النقد الدولي تقديم قروضاً لمساعدة اليونان على تجنب خطر الإفلاس والتخلف عن السداد وذلك مقابل التعهد بتنفيذ الإصلاحات الاقتصادية المنوطة بها. وفي ظل إجواء التفاؤل التي سادت الاتحاد الأوروبي عقب الخروج من الأزمة المالية العالمية، حدث ما لم يتوقع، حيث ظهرت أزمة ديون سيادية هزت كيان منطقة اليورو من داخلها، وبدأت الأسئلة تثار حول طريقة الحل وكيف ستتعامل حكومات هذه المنطقة مع الأزمة. ونظراً لثقل ومكانة منطقة اليورو عالمياً، وضخامة الآثار المتوقعة لأزمة الديون السيادية على اقتصاد هذه المنطقة، كان هذا البحث محاولة لتناول أثر أزمة الديون السيادية على منطقة اليورو بالتحليل والدراسة المعمقة لمفهوم الأزمة وأسبابها والنتائج المتوقعة منها. It threatened the Greek crisis, the stability of the euro zone and raised the idea of ​​a Greek exit from the economic zone after the sovereign debt crisis engulfed the Greek economy in 2010, where the Greek government asked the European Union and the International Monetary Fund to provide loans to help Greece to avoid the threat of bankruptcy and defaults in exchange for pledges to implement economic reforms mandated. In light of the optimism that prevailed after the European Union out of the global financial crisis, an event expected unless, where the sovereign debt crisis in the euro zone appeared entity shaken from within, and the questions began to be raised about the way the solution and how the governments of this region will deal with the crisis. Due to the weight and stature globally euro zone, and the magnitude of the projected sovereign debt crisis on the economy of this region effects, this research is an attempt to address the impact of the sovereign debt crisis on the euro area analysis and study in-depth the concept of the crisis and its causes and expected results.